Local Zeta Functions, Functional Equations and Pseudodifferential Operators Over p-adic Fields (2014)
Abstract. This dissertation is dedicated to study two problems: the first one is the study of Riesz Kernels attached to elliptic quadratic forms of dimensions 4 and 2, and its applications to the construction of fundamental solutions for pseudodifferential operators. The second problem is the study of parabolic-type pseudodifferential equations with variable coefficients in dimension 4